Análise de investimento para a utilização de RFID no gerenciamento de estoque em uma pequena empresa do ramo de cosmeticos - Costa, Fábio Medeiros Cabral (Universidade Federal Rural do Semi-Árido, 2019)
RFID (Radio-Frequency IDentification) technology is a technology of great importance for companies in the logistics sector, providing great competitive advantages, including speed for remote product identification. In this context, the present work aims to identify the feasibility of investing in this technology for a cosmetics company located in the city of Mossoró / RN. For that, financial engineering techniques are used, in order to verify if investment is feasible or not. The techniques used were: NPV (net present value), IRR (internal rate of return), among others, from financial engineering, since from these it is possible to check numerically whether the investment is feasible or not. The results showed that the investment is financially viable since the IRR value of 22% was obtained in the first scenario and 49% in the second scenario and R$ 3,455.50 and R$ 11,286.99 in NPV in the first and second scenario respectively.
Monografia
Keywords: Engenharia financeira; Custos; Investimento; Financial engineering; Costs; Investment; ENGENHARIAS::ENGENHARIA DE PRODUCAO